The SmartAG partner: CCAFS East Africa quarterly newsletter, October–December 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In this issue, we share with you the latest updates on the status of agriculture from the recently concluded nineteenth session of the Conference of the Parties (COP 19) held from 11 to 22 November 2013 in Warsaw, Poland. We also update you on our work with National partners to integrate climate smart agriculture into national level policies and programs. Under the section on science updates, find out how we are working with partners to measure greenhouse gas emissions in soils and our efforts to use climate information to improve farm level decision making. We also share how researchers are applying social learning approaches in Uganda, working with farmers to develop drought resistant bean varieties. Also, find out more about the characteristics of sites where we work, from maps that illustrate climate variability in CCAFS regions. From the field, we update you about the visit with the World Bank team to the CCAFS climate smart villages in Nyando, Kenya. Read more about how to integrate gender and engage with the youth in climate smart agriculture.